ESENSI DAN URGENSI BUMI SEBAGAI RESERVOIR AIR (TINJAUAN TAFSIR EKOLOGI) - Munawarah Munawarah (UIN ANTASARI BANJARMASIN, 2021)
Earth has a major role in maintaining the balance of the water cycle as an essential element of life. However, humans, as agents who should participate in maintaining the balance, do the opposite. Deforestation, irresponsible mining and littering by humans have disrupted the function of the earth as a water reservoir. Climate change, floods, clean water crises, landslides, droughts and ecosystem damage are the impacts. This article aims to explore the main principles in the Qur'an regarding the essence and urgency of maintaining the balance of the earth's role as a water reservoir. In the perspective of ecological interpretation, there are ethical-theological principles in the management of natural resources offered by the Qur'an, namely: First, the principle of al 'adalah is (does not apply persecution to nature and the environment). Second, the principle of al-tawâzun (maintaining the balance of the functions of nature and the environment). Third, the principle of al-intifa’ dûn al-fasad (taking benefits without destroying). Fourth, the principle of al-ri'âyah dûn al-isrâf (use while maintaining and caring for). Fifth, the principle of al-tahdits wa al-istikhlaf (renewal of natural resources that are indeed possible to be renewed). Bumi memiliki peran utama dalam menjaga keseimbangan siklus air sebagai unsur esensial kehidupan. Meskipun demikian, manusia sebagai sebagai agen yang seharusnya turut memelihara keseimbangan itu melakukan tindakan yang sebaliknya. Penggundulan hutan, penambangan tidak bertanggung jawab dan buang sampah sembarangan yang dilakukan manusi menyebabkan fungsi bumi sebagai reservoir air menjadi terganggu. Perubahan iklim, banjir, krisis air bersih, tanah longsor, kekeringan dan kerusakan ekosistem menjadi dampaknya. Artikel ini bertujuan menggali prinsip-prinsip utama dalam Al Qur’an tentang esensi dan urgensi pemeliharaan keseimbangan peran bumi sebagai reservoir air. Dalam perspektif tafsir ekologi, ada prinsip-prinsip etis-teologis dalam pengelolaan sumber daya alam yang ditawarkan al-Qur’an, yaitu: Pertama, prinsip al ‘adalah (tidak berlaku aniaya terhadap alam dan lingkungan). Kedua, prinsip al-tawâzun (menjaga keseimbangan fungsi alam dan lingkungan). Ketiga, prinsip al- intifa’ dûn al-fasad (mengambil manfaat tanpa merusak). Keempat, prinsip al-ri’âyah dûn al-isrâf (mamanfaatkan sembari memelihara dan merawat). Kelima, prinsip al-tahdits wa al-istikhlaf (pembaharuan sumber daya alam yang memang memungkinkan untuk diperbaharui).